O pensamento "sexual" brasileiro a sexualidade melancólica na formação social brasileira - Jose Filho, Fernando [UNIFESP] (2019)
In his book Retrato do Brasil: ensaio sobre a tristeza brasileira, published in 1928, Paulo Prado aimed to build an interpretative history about the social formation of the brazilian people from two distinctive vicious: luxury and greediness. These characteristics ground a melancholic disposition, which are reflected in several choices within the Brazilian society. In front the reading of his work, this research will pay attention specifically to the exame of the lust which it is understood by the autor as a kind of uncontroled sexuality or without moral restraints, as well, the ways in how it can be an helpful element to interpreting Brasil within the brasilian social thought tradition. In this sense, it is also up to this dissertation to point out what Paulo Prado understands by race, sub-race and racial formation, as well as, what the discussions on this theme reverberated in the historical context of production of the studied. Finally, reveal how much the melancolic theory of brasilian sexuality can give us hints to compreend Paulo Prado’s, as well the point of view of an entire generation of intelectuals and politician about an ideal construction of the brasilian society.